2015
DOI: 10.1080/15299732.2014.975308
|View full text |Cite
|
Sign up to set email alerts
|

Trauma, Attentional Biases, and Revictimization Among Young Adults

Abstract: Individuals with previous histories of trauma are at increased risk for subsequent victimization and the development of posttraumatic stress disorder, depression, and anxiety disorders. Attentional biases to threat-related stimuli are thought to impact one's ability to recognize future risk in his or her environment and may explain high rates of revictimization. Although the literature has identified three possible types of attentional biases among victims of trauma (i.e., interference, facilitation, and avoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…This is an indication on which a formal or non-formal university curriculum may have an intervening influence. Somatization, although the reliability of the subscale is low and the result should be viewed with certain reservations, proved to be a significant predictor of the avoiding/adapting style used in social conflict resolution, confirming the theory of the avoidance phenomenon in conflict-handling (Reichert et al, 2015;Shenk et al, 2012;Weeks, 2000;Wilmot & Hocker, 1998). This implies that nursery school teachers who repress unresolved traumatic experiences, manifested as somatization, will probably, in a situation when they should stand up for themselves or the child that has been left in their care, resort to avoiding or retreating and adapting rather than try to solve the problem.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This is an indication on which a formal or non-formal university curriculum may have an intervening influence. Somatization, although the reliability of the subscale is low and the result should be viewed with certain reservations, proved to be a significant predictor of the avoiding/adapting style used in social conflict resolution, confirming the theory of the avoidance phenomenon in conflict-handling (Reichert et al, 2015;Shenk et al, 2012;Weeks, 2000;Wilmot & Hocker, 1998). This implies that nursery school teachers who repress unresolved traumatic experiences, manifested as somatization, will probably, in a situation when they should stand up for themselves or the child that has been left in their care, resort to avoiding or retreating and adapting rather than try to solve the problem.…”
Section: Discussionsupporting
confidence: 53%
“…These are distinctly subjectively unpleasant situations of threatened safety and/or situations that result in the feeling of being overwhelmed and lonely, even if physical symptoms are not present (Arambašić, 1996;Robinson, Smith, & Segal, 2015). With regard to behavioural styles used in social conflicts, Reichert, Segal, and Flannery-Schroeder (2015) note that young persons with traumatic experiences tend to exhibit disruptive, avoidance and adaptive behaviour. Šimić, Sesar, and Barišić (2012) established four groups of trauma symptoms in students, which can result from one or more types of abuse: anxiety and depression, trauma symptoms, somatic symptoms, and sexual problems and difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PTSD symptoms, including anger and disrupted relationships, that follow noninterpersonal trauma might also confer risk for subsequent victimization. Although deficits in risk recognition are most commonly studied in relation to interpersonal trauma, prior work has suggested that risk recognition is not differentially impaired following interpersonal versus noninterpersonal trauma (Reichert, Segal, & Flannery-Schroeder, 2015), which indicates that this mechanism underlying revictimization could extend to individuals who initially experience a noninterpersonal trauma. More research is needed to clarify whether PTSD increases the risk of interpersonal victimization among individuals whose initial trauma was noninterpersonal in nature.…”
mentioning
confidence: 99%
“…The latter criterion became necessary as prior studies considered various developmental stages for revictimization. While most studies define revictimization as victimization in both childhood and adulthood (Arata, 2000; Babcock, 2012; Jankowski et al, 2002), more than one victimization experience in a lifetime, regardless of the age at occurrence, was defined as revictimization by other authors (Matlow & DePrince, 2013; Reichert et al, 2015). Due to the lack of research on the influence of these different age cut-offs on the relationship between revictimization and its risk factors, we cannot assume the results of these studies are comparable.…”
Section: Methodsmentioning
confidence: 99%